Genesis - Longman, Tremper, III (Grand Rapids, Michigan : Zondervan, 2016)
The Story of God Bible Commentary explains and illuminates each passage of Scripture in light of the Bible's grand story. SGBC offers a clear and compelling exposition of biblical texts, guiding everyday readers in how to creatively and faithfully live out the Bible in their own contexts.
Includes bibliographical references and indexes.
Keywords: Bible. -- Commentaries; Bible; Commentaries